The Barriers of Using Video Games as a Media for Teaching and Learning Purposes: A Case Study in Indonesia - Wibowo, Tony; Pee, Ahmad Naim Che; Ahmad, Ibrahim (Universitas Medan Area, 2024)
The 21st century has seen the remarkable growth of the video game industry, which has surpassed other entertainment sectors in terms of financial value. The COVID-19 pandemic further emphasized the importance of video games as a means of socialization and entertainment. However, despite their potential in education, the adoption of video games as a learning media faces numerous barriers. This study explores these barriers, particularly in the context of Indonesia, a country with a burgeoning video game culture. The research uses a mixed-methods approach, including qualitative interviews and quantitative surveys with stakeholders such as parents, teachers, students, and government officials. The findings reveal several key barriers to adopting video games in formal education in Indonesia. There is an inherent mistrust of video games among Indonesians, which makes the use of video games as a learning media challenging. There is a lack of video games designed for educational purposes suitable for Indonesia's formal education system. The lack of government support for video games as learning media also becomes an issue. We suggest collaboration between local game developers and education practitioners could help design video games that balance gameplay mechanics and educational content. Successful case studies of video games in education can potentially change negative perceptions among teachers, parents, and students. In addition, government support and recognition of video games as valid learning media are essential for wider adoption in Indonesia's formal education system. Future research should focus on developing and adopting video games specifically designed for educational purposes to address these barriers effectively